Historical development of the futural and modal system in standard Slovene language from the 16th to the 19th Century - Orožen, Martina (Slavia Centralis, 2021)
The discussion was based on the dissertation with the same title by Martina Orožen, which she defended in 1966 at the Department of Slavic Languages and Literatures at the Faculty of Arts, University of Ljubljana; it is a document of the time in which the dissertation was written and so far the only comprehensive overview of the historical development of the futural and modal system in Slovenia.